A novel 3D hybrid carbon-based conductive network constructed by bimetallic MOF-derived CNTs embedded nitrogen-doped carbon framework for oxygen reduction reaction. (26th January 2022) - Zhang, Yating; Zhang, Nana; Wang, Peng; Shen, Lei; Li, Keke; Li, Siyi; Yang, Mengnan; He, Pei
Abstract: The rational design of novel non-precious oxygen reduction reaction (ORR) electrocatalysts with good catalytic activity for energy conversion devices is under the spotlight of current research. Herein, we designed and fabricated a novel 3D Co-derived CNTs embedded nitrogen-doped carbon framework (denoted as Co-CNTs@NCFT, where T represents the pyrolysis temperature) as an efficient ORR catalyst by pyrolysis of the bimetallic metal-organic framework (MOF) in the presence of graphene oxide (GO). The optimized catalyst furnishes large specific surface area, outstanding electrical conductivity and rapid mass transport rates during reactions. Because of these synergistic advantages, the Co-CNTs@NCF900 exhibits excellent ORR catalytic activity in terms of a high onset potential of 0.96 V and a half-wave potential of 0.84 V in alkaline electrolyte, outperforming the commercial Pt/C. Furthermore, the Co-CNTs@NCF900 manifests good stability and methanol tolerance comparable to the commercial Pt/C catalyst. The presented strategy open up a new avenue for the synthesis of novel electrocatalysts derived from MOF materials for energy-related applications. Graphical abstract: Image 1 Highlights: Uniformly nano-sized bimetallic MOF NPs homogeneously wrapped by graphene sheets. The cobalt-carbon nanoparticles present in CNTs boost the electrocatalytic activity. Co-CNTs@NCF900 could catalyze ORR via a direct 4e − pathway. Co-CNTs@NCF900 delivers superior catalytic activity along with remarkable stability.